THERMO - MECHANICAL MODIFICATION OF AMORPHOUS POLYESTER FIBRES: I. DEFORMATION BEHAVIOUR: THERMO - MECHANICAL MODIFICATION OF AMORPHOUS POLYESTER FIBRES: I. DEFORMATION BEHAVIOUR - Velev , Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The deformation behaviour of as-spun amorphous poly (ethylene terephthalate) (PET) yarns subjected to simultaneous thermal and mechanical treatments has been studied. The samples heat mechanical treatments were realized using constructed and produced in the author’s laboratory device. Thermal deformation experiments were carried out on conditions of linear samples heating from room temperature up to 200 0C while they were subjected to a well-defined constant tensile force. It was observed very interesting and seemingly strange dependence of the final fibre length from the values of the applied tensile stress. The results obtained show the role of the strain stress on the causing samples deformation and in the control of the rival processes of the fluid like deformation and stress-induced crystallization.